Nonvariceal upper gastrointestinal bleeding in patients with liver cirrhosis. Clinical features, outcomes and predictors of in-hospital mortality. A prospective study - González González, José Alberto; García Compeán, Diego; Vázquez Elizondo, Genaro; Garza Galindo, Aldo; Jáquez Quintana, Joel Omar; Maldonado Garza, Héctor Jesús (2011)
Background. Clinical and endoscopic features of cirrhotic patients with nonvariceal upper gastrointestinal bleeding (NVUGIB) have been rarely reported and clinical outcomes and predictors of mortality have not been evaluated. Aims. 1) To describe the clinical features; 2) To define the clinical outcomes; and 3) To identify the predictors of in-hospital mortality of cirrhotic patients with NVUGIB. Methods. One hundred sixty cirrhotic patients with NVUGIB were prospectively studied. Clinical features, endoscopic findings, clinical outcomes and in-hospital mortality rate were studied. Predictors of death were identified by means of univariate and multiple logistic regression analysis. Results. The mean age was 56.5 ± 14.4, male gender prevailed. Alcohol was the most frequent etiology. Hemodynamic instability was reported in 29.4%. Mean serum hemoglobin was 9.5 ± 3.3 g/dL and blood transfusions were required in 59.4%. Gastroduodenal ulcers were the most frequent source of bleeding (50.6%). In endoscopy “high-risk” bleeding stigmata (HRBS) at the ulcer base were found in 53.1%. All patients with HRBS received endoscopic treatment. Rebleeding occurred in 3 patients (1.9%) and mortality was of 13.8%. By univariate analysis: Cryptogenic etiology, BUN, hypoalbuminemia, active bleeding at ulcer base, and endoscopic treatment were predictors of mortality. However, only cryptogenic etiology, hypoalbuminemia and active bleeding at ulcer base were independent predictors of death in multivariate analysis. Conclusions. Gastroduodenal ulcers as a source of NVUGIB are frequent in cirrhotic patients. They were severe; half of them had HRBS, and required frequently endoscopic treatment. In-hospital mortality of these patients seemed to be greater than that of non-cirrhotic patients, and it was significantly related to cryptogenic etiology of cirrhosis, renal dysfunction, severe hepatic failure, and active bleeding ulcers on admission to the hospital.